2021
DOI: 10.1177/02692163211006317
|View full text |Cite
|
Sign up to set email alerts
|

Web and mobile-based symptom management interventions for physical symptoms of people with advanced cancer: A systematic review and meta-analysis

Abstract: Background: Symptom management is a critical aspect of comprehensive palliative care for people with advanced cancer. Web and mobile-based applications are promising e-Health modalities that can facilitate timely access to symptom management interventions for this population Aim: To evaluate the efficacy of web and mobile-based symptom management interventions in alleviating physical symptom burden in people with advanced cancer. Design: A systematic review and meta-analysis was conducted. PROSPERO ID = CRD420… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
1
11
0
1
Order By: Relevance
“…In addition, it also suggests the effectiveness of the workflow to address symptoms scored 4 and above, including the alert, the notification for the primary oncology -129 including improved physical and emotional symptoms, suggesting that these findings were not an artefact of time. 3,7,12,15,27,28 Notably, previous data have shown that patients are receptive to this type of intervention, 9,10 with the exception for older patients who face some challenges with technology. 29 Interestingly, in the present study, age did not impact level of engagement (p = 0.847), nor did level of education, income, race, or distance between patients' home and the cancer center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it also suggests the effectiveness of the workflow to address symptoms scored 4 and above, including the alert, the notification for the primary oncology -129 including improved physical and emotional symptoms, suggesting that these findings were not an artefact of time. 3,7,12,15,27,28 Notably, previous data have shown that patients are receptive to this type of intervention, 9,10 with the exception for older patients who face some challenges with technology. 29 Interestingly, in the present study, age did not impact level of engagement (p = 0.847), nor did level of education, income, race, or distance between patients' home and the cancer center.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, biopsychosocial screening programs have been used to both more effectively identify unmet needs and to gain deeper insight into the nature of symptoms experienced by patients. Notably, eHealth‐based interventions have gained more widespread acceptance due to their ability to mitigate existing barriers (e.g., time, effort, and training) to access 3 . In the current paper, we refer to eHealth as “health service and information delivered or enhanced through the use of the internet and related technologies” and mHealth as the “medical and public health practice supported by mobile devices, such as mobile phones, patients' monitoring devices, personal digital assistants, tablet computers, and/or other wireless devices.” The latter can include voice/short message services or more complex functionalities and applications such as GPS and Bluetooth technologies 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review and meta-analysis study, web-based symptom management interventions were most effective in reducing overall physical symptoms in people with advanced cancer. Physical access barriers, transportation, and due to rapid changes in our environment, such as the COVID-19 pandemic, new technologies have been proposed to support the symptom management of cancer patients [ 40 ]. It was determined that a 12-week individualized education program with online support was effective in preventing cancer-induced fatigue, reducing anxiety, and increasing health-related quality of life [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pemantauan gejala kanker jarak jauh berbasis mobile phone yang sudah sangat dikenal di Negara Eropa yaitu Advanced Symptom Management System (ASyMS) dinilai efektif dalam penurunan gejala fatigue (Odd Ratio= 2,29), penurunan sindrom handfoot (Odd Ratio=0,39) (Kearney et al, 2009) dan penurunan gejala fisik seperti nyeri pada pasien kanker stadium lanjut (Saeidzadeh et al, 2021). ASyMS berbasis mobile phone sudah dilakukan uji klinis, terbukti memberikan manfaat dalam menggurangi kecemasan, dapat mempromosikan self-care dan self-efficacy, mempercepat tenaga kesehatan mengambil keputusan dan intervensi dalam pelayanan kanker (Maguire et al, 2017) Pengembangan pemantauan gejala kanker jarak jauh di Indonesia belum ada.…”
Section: Pendahuluanunclassified